First record of Heimbra bicolor Subba Rao, 1978 (Hymenoptera, Eurytomidae) in São Paulo state, Brazil - Perioto, Nelson W.; Lara, Rogéria I. R. (Entomological Communications, 2021)
Heimbra bicolor Subba Rao, 1978 (Hymenoptera, Eurytomidae) was previously known in Mexico, Argentina, Paraguay, and Brazil, with records in Federal District and Rio Grande do Norte, Minas Gerais, and Santa Catarina states. Here, we newly report this species from the state of São Paulo based on three females collected at Estação Ecológica de Jataí, in the municipality of Luiz Antônio, São Paulo state, Brazil. Additionally, we provide a map with the geographical distribution of the species based on the new record and literature. This record increases the number of species of Heimbra known in São Paulo state to two species.